Distress factors of voice‐hearing in young people and social relating: Exploring a cognitive‐interpersonal voice‐hearing model. (30th June 2022) - Rammou, Aikaterini; Berry, Clio; Fowler, David; Hayward, Mark
Abstract: Objectives: Little is known about the factors that can maintain the distress related to voice‐hearing experiences in youth. Building upon understandings developed with adults, this study aimed to explore the associations between negative relating between hearer and voices, persecutory beliefs about voices and voice‐related distress in a clinical sample of adolescents. The study also aimed to investigate associations between relating to voices and wider patterns of social relating. Design: This was an observational, cross‐sectional, survey study. Methods: Thirty‐four young people (age 14–18 years) who were hearing voices completed measures about voices (characteristics, relating and beliefs) and relating to social others (negative relating styles, social connectedness and belongingness). Participants were patients of NHS mental health services. Bivariate correlations explored associations between relating to voices and distress, beliefs about voices and distress, and between relating to voices and social relating variables. Results: Perceiving the voices as dominant, intrusive, and persecutory and resisting them was significantly associated with distress. Adjusting for loudness and negative content rendered the association between persecutory beliefs and distress non‐significant. Fear of separation and of being alone in relation to social others was associated with distancing from voices. Being suspicious, uncommunicative and self‐reliant and/or being sadistic and intimidating towards social others was significantly associated with dependence towards the voices. Greater hearer‐to‐voice dependence was associated with lower perceived social belongingness and connectedness. Conclusions: Beliefs about voices being persecutory, dominant, intrusive and resisting voices seem to be significant contributors of distress in young people. In terms of proximity and power, relating to voices and social others appears to be contrasting.